Pemetaan Status C-Organik Tanah Sawah Di Desa Sei Bamban, Kecamatan Sei Bamban Kabupaten Serdang Bedagai - Guntur Ompusunggu; Hardy Guchi; Razali Razali (Jurnal Agroekoteknologi, 2016)
This research was heldto know sprending of C-organic on paddy soil land at Village of Sei Bamban Subdistric of Sei Bamban Distric of Serdang Bedagai. This research was executed in Village of Sei Bamban Subdistric of Sei Bamban Distric of Serdang Bedagai on May until August 2015. Samples were taked with method Survey Free Grid of storey level semi detail survey. Parameter which was measured is C organic and analysed with Walkley and Black methods.The results of research were obtained four criteria C-organic nutrient status is very low, low, medium and high. At very low criteria have wide equal to 901,66 Ha. At low criteria have wide equal to 196,34 Ha. At medium have wide equal to 140,10 Ha. At high criteria have wide equal to 0,74 Ha.Keywords: Mapping, C organic, Paddy Soil, Village of Sei Bamban